The effect of intranasal administration of ACTH analogue toward neural progenitor/stem cells proliferation after traumatic brain injury - Loe, Michael Lumintang; Rr. Suzy Indharty,; Siahaan, Andre MP; Tandean, Steven; Riawan, Wibi (Penerbit Universiti Kebangsaan Malaysia, 2020)
Traumatic brain injury (TBI) is a major health problem because of its high mortality and long-term disability worldwide. Neural progenitor/stem cells (NPSCs) that survive in certain parts of the brain, enable brain to produce new neurons and glia. ACTH4-10Pro8-Gly9-Pro10 has a modulation effect on the expression and activation of the BDNF/TrkB system in the hippocampus area. The BDNF/TrkB pathway system is a potential therapeutic target toward NPSCs proliferation after TBI. Thirty male Sprague-Dawley rats were divided into three groups, i.e A=sham-operated controls; B=TBI; C=TBI+intranasal ACTH4-10Pro8-Gly9-Pro10 administration. After 24 h, rats’ brains were immunohistochemically processed, to observe the number of cells expressing mBDNF, TrkB, and SOX2 in the subgranular zone(SGZ) of the hippocampus dentate gyrus(DG). Data were analyzed with SPSS 17, ANOVA, Post Hoc Tukey HSD test, with p value < 0,05. Mean expression of BDNF group C=16.33 ± 2.83 increased significantly compared to group A=8.33 ± 1.32(p=0.0001) and group B=5.89 ±1.69(p=0.0001). Mean expression of TrkB group C=17.00 ± 1.58 increased significantly compared to group A=4.33 ± 1.73(p=0.0001) and group B=5.89 ± 2.47(p=0.0001), TrkB expression in group B increased insignificantly compared to group A (p= 0.234). Mean expression of SOX2 in group C=12.56 ± 2.07 increased significantly compared to group B = 8.89 ±2.318(p=0.0001) and group A=4.89 ± 2.42(p=0.0001). ACTH4-10Pro8-Gly9-Pro10 can increase the expression of BDNF and TrkB, and the proliferation of NPSCs in the subgranular zone (SGZ) of the hippocampus dentate gyrus (DG).